NUDT15 and TPMT polymorphisms in three distinct native populations of the Brazilian Amazon - Perini, Jamila Alessandra; Basta, Paulo Cesar; Suarez-Kurtz, Guilherme (Frontiers in Pharmacology, 2024)
This is the first report of the distribution of TPMT and NUDT15 single nucleotide polymorphisms and metabolic phenotypes associated with cytotoxicity of thiopurine drugs, in indigenous groups of Brazilian Amazon: Munduruku, Paiter-Suruí and Yanomami. The minor allele frequency (MAF) of NUDT15 rs116855232 did not differ significantly across the groups; TPMT rs1800462 was absent, while rs1800460 and rs1142345 were in strong linkage disequilibrium, and 10-and 30-fold more common in Paiter-Suruí. Indeed, the MAFs in Paiter-Surui (0.193 and 0.188) are the largest report globally. The distribution of combined NUDT15/TPMT metabolic phenotypes differed significantly (P < 0.0001) and largely (Cramér´s V = 0.37) across cohorts. This has important pharmacogenetic implications: the Clinical Pharmacogenetics Implementation Consortium recommendations to reduce or consider reduction of thiopurine dose applies to 4.4% Yanomami, 5.6% Munduruku, versus 41% Paiter-Suruí. The proportion of Paiter-Suruí at risk of thiopurine intolerance is 3-to 4-fold higher than any other population worldwide.